QR code based authentication method for IoT applications using three security layers - Abbas M. Al-Ghaili; Hairoladenan Kasim; Marini Othman; Wahidah Hashim (Universitas Ahmad Dahlan, 2020)
A quick response code-based authentication method (QRAM) is proposed. QRAM is applicable for lots of internet of things (IoT) applications. QRAM aims to verify requests of such an access to IoT applications. Requests are made using a quick response code (QRC). To authenticate contents of QRC, users will scan QRC to access IoT applications. To authenticate contents of QRC, three procedures are applied. QRAM contributes to IoT automatic access systems or smart applications in terms of authentication and safety of access. QRAM is evaluated in term of security factors (e.g., authentication). Computation time of authentication procedures for several IoT applications has become a considerable issue. QRAM aims to reduce computation time consumed to authenticate each QRC. Some authentication techniques still face difficulties when an IoT application requires fast response to users; therefore, QRAM aims to enhance so to meet real-time applications. Thus, QRAM is compared to several competitive methods used to verify QRC in term of computation time. Results confirmed that QRAM is faster than other competitive techniques. Besides, results have shown a high level of complexity in term of decryption time needed to deduce private contents of QRC. QRAM also is robust against unauthorized requests of access.